Tay-Sachs: An Ashkenazi Jewish Disease or Not? [26E]. (May 2018) - Echeverri, Natalia; Terhaar, Catherine; Bardos, Jonah D.; Longman, Ryan
Abstract : INTRODUCTION: Tay-Sachs disease (TSD) is an autosomal recessive disorder characterized by progressive neurodegeneration leading to total incapacitation and death by age four. Currently, carrier testing for TSD is recommended for the Ashkenazi Jewish (AJ) population. A joint ACOG/ACMG statement highlighted the increasingly multi-ethnic society as consideration for pan-ethnic carrier testing, and recent ACOG committee opinion states that pan-ethnic carrier testing is a reasonable strategy. This study assesses how many non-AJ Caucasian individuals screened positive for TSD when pan-ethnic carrier screening was implemented. METHODS: Retrospective database analysis of individuals that received expanded carrier testing utilizing a genotyping panel for nine pathologic variants of TSD (1278+TATC, IVS12+1G>C, IVS7+1G>A, IVS9+1G>A, p.G269S, p.R178H, p.R247W, P.R249W, del7.6kb). Expected number of positive carriers for TSD in AJ and Caucasian groups were calculated and compared to observed rates. Chi-square analysis was performed to assess for statistical significance (p < 0.01). RESULTS: A total of 71, 829 individuals were tested for TSD. A higher than expected number of Caucasian individuals screened positive for TSD (110 observed vs 58.48 expected, p<0.001). The number of AJ individuals that screened positive was consistent with expected values (33 observed vs 31.14 expected, p<0.88). CONCLUSION: Caucasian carriers of TSD were more common than expected in this cohort. Pan-ethnic expanded carrier testing will increase the detection of carriers for TSD compared with current ethnicity based screening recommendations. Importantly, carriers of TSD, who would be missed by ethnicity based testing convention, will be identified allowing for more complete genetic counseling and family planning options for those who choose testing.